PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPETEAM ASSISTED INDIVIDUALIZATIONTERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK - Welly Sri Anita (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding ability of mathematical concept is one of the important goals of mathematics learning.In effort to reach the goals, Understanding abillity of mathematical concept can be developed through a learning process. However, in fact found that understanding ability of mathematics concept students of grade XI IPA SMA Negeri 6 Padang is still low. The solution to solve the problem above is to apply cooperative learning model type Team Assisted Individualization. The type of this research is quasy experiment with static group design research design. Population in this research is student of grade XI IPA and the samples are grade XI IPA 5 as experiment class and grade XI IPA 4 as control class. Instrument used in this research is final test of understanding of mathematics concepts student. The result of this research shows that understanding ability of mathematicalconcept student which study with cooperative learning model type Team Assisted Individualization is better than the ability of understanding concepts mathematics student that study with conventional learning in grade XI IPA SMA Negeri 6 Padang.Keywords–understanding ability of mathematical concept, cooperative learning type Team Assisted Individualization, conventional learning